Myomectomy in infertile women: More harm than good? - Mercorio, Antonio; Della Corte, Luigi; Boccia, Dominga; Palumbo, Mario; Reppuccia, Sabrina; Buonfantino, Cira; Cuomo, Lara; Borgo, Maria; Zitiello, Antonio; De Angelis, Maria Chiara; Laganà, Antonio Simone; Bifulco, Giuseppe; et al. (Frontiers in Surgery, 2023)
Adhesion formation following gynecological surgery remains a challenge. The adoption of minimally invasive surgical approaches, such as conventional or robotic-assisted laparoscopy combined with meticulous microsurgical principles and the application of adhesion–reducing substances, is able to reduce the risk of de novo adhesion formation but do not eliminate it entirely. Myomectomy is the most adhesiogenic surgical procedure and postoperative adhesions can have a significant impact on the ability to conceive. Therefore, when surgery is performed as infertility treatment, attention should be paid to whether the benefits outweigh the risks. Among several factors, the size and the location of fibroids are the most accountable factors in terms of adhesion development and post surgical infertility; therefore, the search for effective strategies against adhesion formation in this setting is of paramount importance. The purpose of this review is to evaluate the incidence and factors of adhesion formation and the best preventive measures current available.